State of world rural poverty: a profile of Latin America and the Caribbean - Haralambous, Sappho ed. (International Fund for Agricultural Development RomeIT, 1993)
Presents a profile of poverty in Latin America and the Caribbean. Looks at poverty processes and makes suggestions for overcoming poverty in Latin America and the Caribbean.